PERBANDINGAN KARAKTER NASIONALIS ANTARA SISWA YANG BERETIS TIONGHOA DENGAN SISWA ETNIS MELAYU KELAS XI SMA NEGERI 2 DABO SINGKEP TAHUN PELAJARAN 2013-2014 - Nurmi Vadilah Vadilah; Zahirman '; Hambali ' (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2015)
Abstract: This research background by the nationalist flavor differences between ethnic Chinese students with students who are ethnic Malays, who are ethnic Malay necessarily use basic characteristics in daily life the character of nationalism. However, students who are ethnic Chinese have a different character is a character that is still used strictly in the household environment and daily life. Vocabulary of the language is very different from the Indonesian. So writer take the title "Comparison Between Character Nationalist Chinese Students Beretis With Ethnic Malay Class XI student of SMAN 2 Dabo Singkep Academic Year 2013-2014". Formulation of the problem in this research is the nationalist character How significant differences between ethnic Chinese students with ethnic Malay students? This study aims to determine how the nationalist character differences between ethnic Chinese students with ethnic Malay students. The sample consists of all students in grade XI, both grade IPA and IPS SMAN 2 Dabo Singkep which amounted to 140 students and 118 students were taken. Data collection instruments, namely a questionnaire consisting of 39 questions. Data were analyzed using t-tests. Based on the analysis of research data obtained from SMA Negeri 2 Dabo Singkep, there are no significant differences. In other words, the nationalist character of ethnic Chinese students with ethnic Malay students is the same as karegori very strong, t = 1.26 <t table 1,658. Thus Ho accepted. So, based on data testing the hypothesis of the study was not proven. Keywords: Character Nationalist, ethnic Chinese, Malay Ethnicity